Mutant p53 and ETS2, a Tale of Reciprocity - Martinez, Luis Alfonso (Frontiers in Oncology, 2016)
TP53 is one of the most frequently inactivated tumor suppressor genes in human cancer. However, unlike other tumor suppressor genes whose expression is lost, TP53 is usually inactivated as a result of a single nucleotide change within the coding region. Typically, these single nucleotide mutations result in a codon change that creates an amino acid substitution. Thus, unlike other tumor suppressor genes whose expression is lost due to genetic or epigenetic changes, the p53 gene primarily suffers missense mutations, and therefore, the cells retain and express a mutant form of the p53 protein (mtp53). It is now well established that mtp53 contributes to tumor development through its gain-of-function (GOF) activities. These GOF activities can arise from novel protein–protein interactions that can either disable other tumor suppressors (e.g., p63 and p73) or enable oncogenes such as ETS2, an ETS family member. In this review, I will focus on the identification of the mtp53/ETS2 complex and outline the diverse activities that this transcriptional regulatory complex controls to promote cancer.